Numerical Study of Multilayer Planar Film Structures for Ideal Absorption in the Entire Solar Spectrum - Wei Chen; Jing Liu; Wen-Zhuang Ma; Gao-Xiang Yu; Jing-Qian Chen; Hao-Yuan Cai; Cheng-Fu Yang (Applied Sciences, 2020)
Here, we have theoretically proposed an ideal structure of selective solar absorber with multilayer planar films, which can absorb the incident light throughout the entire solar spectrum (300–2500 nm) and over a wide angular range, whatever the polarization angle of 0°~90°. The efficiency of the proposed absorber is proven by the Finite-Difference Time Domain (FDTD) simulation. The average absorption rate over the solar spectrum is up to 96.6%. The planar design is extremely easy to fabricate and modify, and this structure does not require lithographic processes to finish the absorbers. Improvements of the solar absorber on the basis of planar multilayer-film structures is attributed to multiple asymmetric highly lossy Fabry–Perot resonators. Because of having many virtues, such as using different refractory and non-noble metals, having angle and polarization independence, and having ideal absorption for entire solar spectrum, our proposed absorbers are promising candidates for practical industrial production of the solar-energy harvesting.